2017
DOI: 10.1097/bot.0000000000000728
|View full text |Cite
|
Sign up to set email alerts
|

Does a Staged Posterior Approach Have a Negative Effect on OTA 43C Fracture Outcomes?

Abstract: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…After a minimum 1-year follow-up, the articular reduction and ankle function score improved in the staged posterior tibial plating group much better than in the direct anterior tibial plating group. However, after prolonged clinical study, Chan et al reported that addition of the staged posterior approach did not benefit the articular reduction but significantly increased the risk of nonunion [4]. Consequently, the best way to balance the articular reduction with the multiple complications of fracture healing and ankle function should be further explored.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After a minimum 1-year follow-up, the articular reduction and ankle function score improved in the staged posterior tibial plating group much better than in the direct anterior tibial plating group. However, after prolonged clinical study, Chan et al reported that addition of the staged posterior approach did not benefit the articular reduction but significantly increased the risk of nonunion [4]. Consequently, the best way to balance the articular reduction with the multiple complications of fracture healing and ankle function should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Combined approaches provide sufficient articular visualization, facilitating both reduction and fixation. However, one study reported that the combined approaches possibly increased the risk of fracture healing and soft tissue complications [4]. The reason may be that the combined approach increases surgical stripping and damage to the blood supply of bone tissue.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations